The use of nanostructured materials loaded with pH indicating molecules for corrosion sensing - Sousa, Isabel (2018)
In this work we report the synthesis of different materials for immobilization of well-known pH indicators, to be used as additives in coatings for corrosion sensing: inorganic materials such as layered double hydroxides, silica nanocapsules and polymeric microcapsules (chitosan). The materials obtained were characterized by X ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopies. Furthermore, the release profile of the obtained materials was performed using UV-Visible spectrophotometry under conditions relevant for the onset of corrosion processes, namely in the presence of NaCl and different pH conditions. The release and color changes were correlated with pH maps obtained by the scanning ion-selective technique for different galvanic couples (Al-Cu, Fe-Zn) and magnesium alloy AZ31. The results show that the materials obtained are able to change color, associated with the pKa of selected indicators and ascribed to pH changes in the alkaline direction as result of cathodic activity in different metals. These findings open prospects for the use of the prepared additives in functional coatings for corrosion sensing.